Social Media Marketing and Brand Equity That Affect Consumer Buying Interest of Geoff Max Products in Bandung - Hapsari, Ayuningtyas Y.; Pratama, Dewa G.Abikanda; Ananda, Agil; Febriani, Fauzy; Allaudin, Abid; Saputra, Ari Akbar (CENTRAL ASIA AND THE CAUCASUS, 2022)
Geoff Max is one of a famous local shoes brand in Indonesia. There are doing penetrated overseas with the enactment of online transactions, because for Geoff Max it is not enough just to have a brand, design and label but the output of the shoe product itself must also have quality and product quality that is maintained and prioritized. creative innovation with unique characteristics so that the Geoff Max brand can survive and have permanent and loyal consumers from time to time. As one of the most popular local shoe products in the city of Bandung. the strong brand that was raised by Geoff Max by appointing a celebrity as his endorser, this did not create a desire or interest to buy among consumers who had never purchased the product, but these consumers knew and even received recommendations from the closest people about this Geoff Max products. For processing and analyzing data in this study, using SPSS 20 as software to process data. The data obtained is by using a random sampling technique, then an analysis of the data obtained with qualitative data is carried out. Quantitative analysis includes: Multiple regression analysis, hypothesis testing through t test, and simultaneous hypothesis testing. Based on the data obtained, the two independent variables (Social Media Marketing and Brand Equity) have an influence on the dependent variable (Consumer Buying Interest).